Agronomic behaviour of strawberry genotypes subjected to different cultivation methods - Sampietro, Ana Paula; Oliveira, Luiz Fernando de Jesus; Lima, Claudia Simone Madruga; Santos, Elaine Rodrigues dos; Leandrini, Josimeire Aparecida; Lemos, Pedro Luiz Panisson Kaltbach (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
The objective of this work was to evaluate the agronomic performance of two strawberry genotypes submitted to different cultivation technologies in an organic production system. The genotypes tested were CREA FRF LAM 269.19 (short-day) and CREA FRF 114.01(day-neutral). The plants were grown in soil, troughs, slabs and pots. The experimental design was completely randomized in a factorial arrangement. The parameters evaluated were: dates of bloom onset, fructification and harvesting; several plant features; several fruit features; and yield components - total production; number of fruits, commercial production; production of small fruits and; total productivity. The day-neutral genotype allowed earlier onset of harvesting and greater vegetative development. Trough and bed cultivation provided higher fruit yield and quality in both genotypes. In beds, the fruits presented higher soluble solids content in both genotypes. In sum, the day- neutral genotype associated with the cultivation in beds provided the best agronomic performance in an organic cultivation system.